The ecology of herd immunity - Dias de Avila-Pires, Fernando (Revista de Patologia Tropical / Journal of Tropical Pathology, 2021)
The COVID-19 pandemic that began in early 2020 is currently the subject of thousands of articles on the various aspects of its epidemiology. One recurrent theme is the phenomenon of herd immunity or herd effect. In this article, I present a short history of the concept, the arguments around its nomenclature, and the ecologist’s view of the herd effect, using the case history of the sleeping sickness control in Africa. KEY WORDS: Herd immunity; convergence; ecology; sleeping sickness.